TEXTBOOKS AND PEDAGOGY IN THE BEGININGS OF THE XXTH CENTURY, IN COLOMBIA (2012)
In the first three decades of the 20th century, the school textbooks were in in order to promote political, ideological and pedagogic projects. On the elementary school texts of education of the language, particularly, the juridical regulations are investigated in all that it has to see with the educational normativity, the ideal ones, the principles, the methods and the practices of education. Likewise, the fights are recognized in the school texts concerning the ideologies that they support for the way in which it is necessary to train the citizens and in the guidelines to construct a type of Nation.